Localized Modification of Water Molecule Transport After Focused Ultrasound-Induced Blood–Brain Barrier Disruption in Rat Brain - Han, Mun; Seo, Hyeon; Choi, Hyojin; Lee, Eun-Hee; Park, Juyoung (Frontiers in Neuroscience, 2021)
Interstitial solutes can be removed by various overlapping clearance systems, including blood–brain barrier (BBB) transport and glymphatic clearance. Recently, focused ultrasound (FUS)-induced BBB disruption (BBBD) has been applied to visualize glymphatic transport. Despite evidence that FUS–BBBD might facilitate glymphatic transport, the nature of fluid movement within the sonication region is yet to be determined. In this study, we sought to determine whether FUS–BBBD may facilitate the local movement of water molecules. Two different FUS conditions (0.60–0.65 MPa and 0.75–0.80 MPa) were used to induce BBBD in the caudate-putamen and thalamus regions of healthy Sprague–Dawley rats. The water diffusion caused by FUS–BBBD was analyzed using the apparent diffusion coefficient (ADC), axial diffusivity, radial diffusivity (RD), and fractional anisotropy, obtained at 5 min, 24 and 48 h, as well as the water channel expression of aquaporin-4 (AQP-4) immunostaining at 48 h after FUS-induced BBBD. In addition, hematoxylin and eosin histopathology and Fluoro-Jade C (FJC) immunostaining were performed to analyze brain damage. The signal changes in ADC and RD in the sonication groups showed significant and transient reduction at 5 min, with subsequent increases at 24 and 48 h after FUS-induced BBBD. When we applied higher sonication conditions, the ADC and RD showed enhancement until 48 h, and became comparable to contralateral values at 72 h. AQP-4 expression was upregulated after FUS-induced BBBD in both sonication conditions at 48 h. The results of this study provide preliminary evidence on how mechanical forces from FUS alter water dynamics through diffusion tensor imaging (DTI) measures and AQP4 expression.